2003
DOI: 10.1074/jbc.m212096200
|View full text |Cite
|
Sign up to set email alerts
|

Mutational Analysis of the Non-homologous Region of Subunit A of the Yeast V-ATPase

Abstract: Subunit A is the catalytic nucleotide binding subunit of the vacuolar proton-translocating ATPase (or V-ATPase) and is homologous to subunit ␤ of the F 1 F 0 ATP synthase (or F-ATPase). Amino acid sequence alignment of these subunits reveals a 90-amino acid insert in subunit A (termed the non-homologous region) that is absent from subunit ␤. To investigate the functional role of this region, site-directed mutagenesis has been performed on the VMA1 gene that encodes subunit A in yeast. Substitutions were perfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
51
0
2

Year Published

2003
2003
2015
2015

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 60 publications
(54 citation statements)
references
References 76 publications
1
51
0
2
Order By: Relevance
“…Specifically, it is conceivable that PKA phosphorylation of the A subunit modulates protein-protein interactions within the multisubunit V-ATPase complex and/or with other interacting proteins involved with cellular trafficking of the pump. For example, the sequence around our identified PKA phosphorylation site is highly conserved in eukaryotes and lies within a so-called "non-homologous" region (63). This region received its name because it is not present in the F-ATPase ␤ subunit, which otherwise has high homology to the V-ATPase A subunit.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, it is conceivable that PKA phosphorylation of the A subunit modulates protein-protein interactions within the multisubunit V-ATPase complex and/or with other interacting proteins involved with cellular trafficking of the pump. For example, the sequence around our identified PKA phosphorylation site is highly conserved in eukaryotes and lies within a so-called "non-homologous" region (63). This region received its name because it is not present in the F-ATPase ␤ subunit, which otherwise has high homology to the V-ATPase A subunit.…”
Section: Discussionmentioning
confidence: 99%
“…Although the salicylihalamide effect in vivo is consistent with previous observation that inhibition of V-ATPase activity in yeast through mutagenesis blocks dissociation (19,34), the correlation between the activity of V-ATPase and its reversible dissociation has not been clearly established. Mutagenesis studies with subunit D showed that a mutant with only 6% of wild-type level of proton pumping activity still demonstrated normal dissociation in response to glucose deprivation (35), whereas some mutations in subunit A resulted in a partial or complete blocking of dissociation despite possessing more than 30% of wild-type levels of activity (25). In this context, our observation that reversible salicylihalamide analog 14 at the lower dose did not induce the cellular V 1 redistribution response reminiscent of salicylihalamide A, but behaved more like bafilomycin, suggests that the unique response with salicylihalamide might be related to its unique inhibition characteristics.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the yeast vacuolar H ϩ -ATPase A subunit possesses a stretch of an additional 90 amino acids compared with ␣-subunits. This additional segment may play a role in the coupling efficiency of ATP hydrolysis to proton transport and the dissociation of V 1 and V 0 complexes (461).…”
Section: The V 1 Domainmentioning
confidence: 99%